Proceedings of the 47th ACM Technical Symposium on Computing Science Education 2016
DOI: 10.1145/2839509.2844584
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Approach to Enhancing Compiler Error Messages

Abstract: Publication information SIGCSE '16 Proceedings of the 47th ACM Technical Symposium on Computing Science EducationConference details ABSTRACTOne of the many challenges novice programmers face from the time they write their first program is inadequate compiler error messages. These messages report details on errors the programmer has made and are the only feedback the programmer gets from the compiler. For students they play a particularly essential role as students often have little experience to draw upon, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 22 publications
3
52
0
10
Order By: Relevance
“…We show that RED is reduced in an empirical control/intervention study, providing evidence that this metric is valid. Reductions in EQ and RED also support the results of [3] and [4], providing further evidence that enhancing error messages is effective. We also discuss some threats to validity.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…We show that RED is reduced in an empirical control/intervention study, providing evidence that this metric is valid. Reductions in EQ and RED also support the results of [3] and [4], providing further evidence that enhancing error messages is effective. We also discuss some threats to validity.…”
Section: Introductionsupporting
confidence: 70%
“…The control group experienced the normal JDK compiler errors while the intervention group experienced enhanced errors provided by the editor based on the JDK error and the student code. This editor was found, with the same data set, to significantly reduce the overall number of student errors, the number of errors per student, and the amount of repeated student errors per compiler error message [4]. Of course RED is just one of many possible metrics that could be developed to measure repeated errors.…”
Section: Application To Student Datamentioning
confidence: 96%
See 1 more Smart Citation
“…In previous work (Becker, 2016a) we showed that there was a significant reduction in the number of errors encountered by an intervention group that received ECEMs compared to a control group that did not. We also reported preliminary evidence that the number of repeated errors was significantly reduced.…”
Section: Compiler Error Enhancementmentioning
confidence: 79%
“…This is evidence that students in both groups were behaving similarly in the absence of ECEMs. In (Becker, 2016a) we investigated the 15 most frequent CEMs and found that of these, nine had a statistically significant reduction in the number of errors per student. These are presented in Table 5.…”
Section: Do Ecems Reduce the Number Of Errors Per Student?mentioning
confidence: 99%